Marketing Analysis of Tourism Destinations at Cisoka Eco Green Park - Karmila, Ila; Hidayat, Cahya; Rorensia, Nazwa Mallika; Nazmi, Putri Nur; Fitriyani, Rossa (Journal of Bussines Management Basic, 2026)
Cisoka Eco Green Park, located in Sumedang Regency, is developed as a nature tourism destination with a focus on ecotourism, based on the principles of environmental conservation, education, and local community empowerment. This study aims to examine the management and marketing strategies of the area through the 7P marketing mix approach. The research method used is qualitative, including observation, interviews, documentation collection, and data triangulation. The study results show that this tourist attraction provides various facilities such as camping areas, villas, a canteen, a prayer room, and photo spots, with an affordable ticket price of Rp5,000, thus supporting visitor comfort. Its strategic location amid tea plantations and the effective use of digital marketing are additional attractions. The involvement of the local community in managing creative economy initiatives also strengthens the sustainability of this destination. In conclusion, Cisoka Eco Green Park has great potential as a leading ecotourism destination with a concept that balances recreation and environmental conservation, and its marketing strategy is able to build visitor loyalty while supporting sustainable development.